Feature extraction from digitized images of dye solutions as a model for algal bloom remote sensing - Punzalan, Eric R. (Animo Repository, 2013)
Digital images of dye solutions were obtained under controlled conditions to simulate images of algal blooms. The images were dissected and analyzed using RGB color space to determine color feature-pigment concentration correlations. The results indicate that the technique may be used in the determination of algal bloom levels / water pigmentation by application of the same analysis to aerial photos of HAB affected bodies of water.